Geoelectric model of the crust and upper mantle along DSS profile Novoazovsk—Titovka - I. Logvinov; V. Tarasov (Геофизический журнал, 2015)
The results of two-dimensional inversion of magnetoteluric data, focused along the DSS profile Novoazovsk—Titovka have been presented. On the territory of Donbas two objects have been distinguished with low resistance (causing Donbass conductivity anomaly) which occur: in the southern part in sedimentary rocks (at a depth of 1—10 km), in the central part (at a depth of 1—18 km) in sedimentary rocks and penetrating into consolidated crust. Total cumulative integral conductivity of the objects is about 3×108 S×m. The most reliably the objects spatially correlate with the coal-bearing rocks of the Carboniferous.